RELATIONSHIP BETWEEN HEALTH BEHAVIORS AND INCIDENT OF DENGUE FEVER AND DHF IN THEWORKING AREA OF SINGOSARI PEMATANG SIANTAR HEALTH CENTER - Shofian Syarifuddin; Wilson Samosir (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2022)
The background in this study is that Dengue Hemorrhagic Fever (DHF) is a public health problem in Indonesia, since 1968 the number of cases has tended to increase and its spread has become wider. The incidence of Dengue Hemorrhagic Fever (DHF) in the working area of ​​the Pematang Raya Health Center in 2008 was recorded as many as 91 cases with 2 fatalities. From the data obtained, it is known that there was a significant increase in the incidence of Dengue Hemorrhagic Fever (DHF) from year to year between 2004-2008. The purpose of this study was to determine what health behaviors were associated with the occurrence of Dengue Hemorrhagic Fever (DHF) in the working area of ​​the Pematang Raya Public Health Center. This type of research was an analytic survey study using a case-control approach. The population in this study were Dengue Hemorrhagic Fever sufferers (cases) and not Dengue Hemorrhagic Fever sufferers (controls). A sample of 40 cases and 40 controls were obtained using simple random sampling technique. The instruments used in this study were 1) questionnaires, 2) data on DHF patients at the Pematang Raya Health Center and DKK Kendal. The data for this study were obtained from primary data, in the form of interview results, and secondary data in the form of DHF patients at the Pematang Raya Health Center and DKK Kendal. The data obtained in this study were analyzed using the Chi-square statistical test formula and the determination of the Odds Ratio (OR). From the research results it was found that the significant factors were: cleaning the water reservoir (p value-0.044, OR=2.513), closing the water reservoir (p value 0.002, OR=4.333), draining water reservoirs (p value 0.004, OR=3.857), burying used goods (p value 0.014, OR-3.095), throwing garbage in its place and burning it (p value-0.043, OR=2.538), hanging clothes (p value=0.001, OR=4.896), and use mosquito repellent lotion (p value=0.002, OR=6.000). From the results of the research and discussion, it can be concluded that health behaviors related to the incidence of Dengue Hemorrhagic Fever (DHF) in the 2018 Pematang Raya Health Center work area, namely cleaning water reservoirs, closing water reservoirs, draining water reservoirs, burying used goods , throwing trash in its place and burning it, hanging clothes, and wearing mosquito repellent.